The Role of Generative AI in Adaptive Learning: Innovations in the *Merdeka* Curriculum at Private Islamic Higher Education Institutions - Retno Fentari (EDUJAVARE: International Journal of Educational Research, 2026)
The Merdeka Curriculum promotes more adaptive, flexible, and student-centered learning. In this context, artificial intelligence (AI) technology particularly generative AI is beginning to be utilized by instructors in the Elementary Madrasah Teacher Education program to tailor learning materials, methods, and assessments. This study seeks to explore how generative AI is applied in adaptive learning at the higher education level. The study aims to determine the level of understanding, frequency of use, and lecturers' perceptions regarding the effectiveness and challenges of using generative AI in the implementation of the Merdeka Curriculum. A descriptive quantitative approach was used in this study, involving 8 lecturers from the University of Islam Lampung. Data were collected through observation, interviews, and documentation and analyzed descriptively.The results show that most lecturers in Elementary Madrasah Teacher Education have a good understanding of generative AI, with a fairly high frequency of use in the teaching process. Lecturers' perceptions of AI's effectiveness in supporting adaptive learning are generally positive, although some challenges such as limited internet access and a lack of technical training are still being experienced. Generative AI contributes to strengthening the implementation of the Merdeka Curriculum by providing more personalized and flexible learning experiences. This study highlights the need for policy support and ongoing training to ensure that the use of AI in education can be optimized